2005
DOI: 10.1206/0003-0082(2005)498[0001:nssdea]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

New Stratigraphic Subdivision, Depositional Environment, and Age Estimate for the Upper Cretaceous Djadokhta Formation, Southern Ulan Nur Basin, Mongolia

Abstract: Studies of key and newly discovered sections of the Upper Cretaceous Djadokhta Formation along the southern margin of the Ulan Nur Basin allow a new subdivision based on lithology. The formation and its members were mapped at both Bayn Dzak, an area that includes the Flaming Cliffs, and Tugrugyin Shireh, an area about 50 km to the northwest of Bayn Dzak. Stratigraphic sections at both localities were remeasured. The considerably enlarged formation comprises a lower Bayn Dzak Member, dominated by moderate reddi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 21 publications
1
79
1
Order By: Relevance
“…Dingus et al (2008) carefully documented the geology of the Ukhaa Tolgod beds and suggested a Campanian age for these sediments. This is in general agreement with previous studies of this and other Djadokhta localities (Lillegraven and McKenna, 1986;Averianov, 1997;Gao and Norell, 2000;Dashzeveg et al, 2005). These correlative Djadokhta localities include the red sandstones at Bayn Dzak (Berkey and Morris, 1927) and the white sands of Tugrikin-Shireh (Fastovsky et al, 1997), both in the Middle Gobi near the town of Dalandzadgad.…”
Section: Discussionsupporting
confidence: 91%
“…Dingus et al (2008) carefully documented the geology of the Ukhaa Tolgod beds and suggested a Campanian age for these sediments. This is in general agreement with previous studies of this and other Djadokhta localities (Lillegraven and McKenna, 1986;Averianov, 1997;Gao and Norell, 2000;Dashzeveg et al, 2005). These correlative Djadokhta localities include the red sandstones at Bayn Dzak (Berkey and Morris, 1927) and the white sands of Tugrikin-Shireh (Fastovsky et al, 1997), both in the Middle Gobi near the town of Dalandzadgad.…”
Section: Discussionsupporting
confidence: 91%
“…Yet, similar to the classic Djadokhta exposures at Bayn Dzak, the sequence of strata at Ukhaa Tolgod reflects a mixture of facies E-1, E-2, F, and S in the lower part of the section, with prominent beds of Facies C near the top (Gradziń ski et al, 1969(Gradziń ski et al, , 1977Gradziń ski, 1970;Dashzeveg et al, 2005). Dashzeveg et al (2005) refer the exposures at Bayn Dzak to the Bayn Dzak Member of the Djadokhta Formation.…”
Section: Calculation Of Local Dip and Its Implication For The Stratigmentioning
confidence: 75%
“…In the three-bin approach, if taxa were known from the first and third time bin, then they were also assumed to be present in the intervening time bin. The Djadokhta Formation is here considered to be late Campanian in age and the overlying Nemegt Maastrichtian, following the latest work on Asian Late Cretaceous stratigraphy 49,50 . There is some uncertainty regarding whether the Nemegt is entirely Maastrichtian or if its base may be late Campanian in age.…”
Section: Methodsmentioning
confidence: 99%